Methane Concentration Influence on Combustion in a Rapid Compression Machine under DFICE Relevant Conditions - Clemente Mallada, Rafael; Peter, Andreas; Rieß, Sebastian; Strauß, Lukas; Fajri, Hamidreza; Wensing, Michael (Journal of Mechanics Engineering and Automation, 2023)
In this experimental work, an optically accessible rapid compression machine is used to study the ignition and combustion process under engine relevant operation conditions for five different air-natural gas equivalence ratios (λ) ignited with either 12.2 mg or 6.7 mg of pilot diesel injected at 1,600 bar. Initial temperature of the ambient mixture, walls and injector was 333 K. Additionally, for the short (6.7 mg) diesel injection, the variation in the ID (ignition delay) for two higher ambient temperatures (343 K and 353 K) was measured. Pressure and piston displacement are recorded while two high-speed cameras simultaneously capture signals in the visible range spectrum and at 305 nm wavelength for OH* chemiluminescence respectively. ID is measured both from OH* and pressure rise. From the recorded data, the heat release ratio is estimated and compared with the visual signals. This gives an insight of the temporal and spatial evolution of the flame, as well as a qualitative perception of the transition from spray ignition into a premixed flame in the ambient fuel-air mixture. It was found that increasing the methane concertation delays the ignition, reduces the natural flame luminosity and enhances the OH* chemiluminescence signal.<br
Keywords: Dual-fuel; natural gas; diesel; rapid compression machine

Methanol – n-dodecane dual-fuel direct-injection combustion under compression ignition conditions in a constant flow chamber - Clemente Mallada, Rafael; Fajri, Hamidreza; Rieß, Sebastian; Strauß, Lukas; Wensing, Michael (ICLASS 2024 - 16th Triennial International Conference on Liquid Atomization and Spray Systems, 2024)
This experimental work visualizes the mixture preparation, ignition, and combustion of methanol (MeOH) and n-dodecane sprays colliding at an angle of 0.42 radians at an ambient temperature of 873K and density of 23.4 kg/m³. High-speed Schlieren imaging experiments are conducted in an inert atmosphere to study the resulting mixture formation from the collision of the two vapor jets. Schlieren and OH* high-speed imaging of the flames allow for the investigation of ignition delay (ID) and heat release ratio (HRR). High-speed imaging of the natural luminosity of the flames allows for the comparison of soot production. Three distinct injection strategies are investigated: (1) injecting MeOH into a flame of the pilot fuel (PF), (2) timing both injections to reach the intersection point simultaneously, and (3) injecting the PF into an already stratified methanol plume. To study the influence of the substitution ratio, MeOH electronic injection duration is varied from 550 μs to 3000 μs, and the PF duration is shortened from 270 μs to 190 μs. PF is injected at 80MPa and 160MPa to study the influence of PF’s spray momentum compared to the MeOH spray injected at 35 MPa. Results demonstrate the possibility of sustaining a MeOH flame. Cases where the PF sprays ignite after colliding with the MeOH jet exhibit a reduction in soot production and a prolonged

Mixture Formation Analysis for Diesel, n-Dodecane, RME, and HVO in Large-Scale Injector Nozzles - Fajri, Hamidreza; Clemente Mallada, Rafael; Rieß, Sebastian; Strauß, Lukas; Wensing, Michael (CO2 Reduction for Transportation Systems Conference, 2022)
Momentum conservation is a principle rule that affects the behaviour of vapour jet and liquid spray penetration. The air entrainment and mixture formation processes are dominated by the momentum transferred from the fuel to the ambient gas. Thus, it is a significant factor in the development of spray and jet penetration. This mixture formation process is well described for small-scale passenger car injectors; however, it has to be investigated in more detail for large-scale injector nozzles. The current work provides qualitative and quantitative results of spray and jet parameters in a constant volume combustion chamber (CVC). Two optical methods have been utilized to evaluate spray and jet details: Schlieren photography as a method to visualize the jet penetration and cone angle as well as Mie scattering for the phase change evaluation and the determination of liquid spray parameters. The temperature and pressure of inert gas and fuel inside a CVC are set to exemplify engine conditions. The chamber temperature is ranged between 873 to 973K, the chamber pressure is increased from 5 to 7 MPa and the injection pressure is changed between 50 to 150 MPa. Four fuels are selected in order to shed light upon the effects of fuel properties on spray and jet parameters. As a part of this evaluation, n-dodecane and two types of bio-diesel fuel generations, RME (1st Generation) and HVO (2nd Generation) are dissected to expand their influences on mixture formation, which can be connected to the emission production in diesel engines. Finally, two large-scale injector nozzles with an outlet hole diameter of 300 μm (cylindrical and conical nozzles) cover the effects of geometry parameters on spray and jet development. The results accentuate the fact that the liquid spray parameters are effectively fuel-dependent, while total jet parameters are mostly affected by nozzle geometry. Liquid spray length is varied from n-dodecane as a low-boiling fuel to RME as a less-volatile fuel. The conical nozzle results in less cavitation, which is effectively influential on liquid spray and total jet penetration
Keywords: ICE; Large Scale Nozzel; Fuel; Mixture Formation

Optical measurements of two cylindrical and conical heavy-duty diesel injector nozzels – A comparison of reference diesel, HVO, and RME fuels - Fajri, Hamidreza; Rieß, Sebastian; Clemente Mallada, Rafael; Ruoff, Ilona; Wensing, Michael (Energy Conversion and Management, 2023)
In the present work, a constant volume/constant pressure combustion chamber was utilized to measure the major parameters of vapour/liquid phases and combustion of fuel spray introduced by two heavy-duty, large-diameter diesel injectors. A conical nozzle (K factor 4) with a 300 µm outlet diameter and a 1300 µm length and a cylindrical nozzle (K factor 0) with a 300 µm outlet diameter and a 650 µm length display notably distinct impacts on the formation of the mixture, the air entrainment process, and the combustion behaviour. Several parameters, including jet and liquid spray penetration lengths, jet cone angle, and jet projected area are combined to describe spray characteristics in an inert background gas, and ignition incidence, flame lift-off length, and soot appearance time parameters are calculated to explain the combustion trend of the nozzles in a reactive gas background. These observations were conducted using four distinct optical techniques, two of Schlieren and Mie-Scattering for inert condition, and two of OH* Chemiluminescence and Natural Flame Luminosity for reactive condition. This study collects a wide variety of boundary conditions, comprising ambient pressure/temperature and fuel rail pressure, with diverse fuels, including reference diesel, HVO, and RME fuels. The findings are categorized by the jet and liquid spray behaviours in the first part, demonstrating that the jet cone angle is an injector geometry-based parameter and that the cylindrical nozzle has a larger cone angle and a shorter liquid spray length. Three distinct scenarios of the computed air-to-fuel mass ratio at the same axial positions, time steps, and injected fuel mass indicate a marginally higher air entrainment in the cylindrical nozzle and, presumably, a faster and better mixture formation. The thorough examination of the combustion characteristics indicates that a quicker formation of the initial stoichiometric region in the cylindrical nozzle results in a shorter ignition delay at most experimental locations, which ultimately results in a faster soot initiation. However, depending on the flame lift-off length and the boundary conditions, the interval between ignition and the development of soot varies considerably. Finally, it is demonstrated that, with the exception of fuel pressure variation, the flame lift-off length, which is crucial in providing the initial mixture formation prior to combustion occurrence, follows the ignition delay trend and exhibits a shorter length with a shorter ignition delay.
Created from Fastlane, Scopus look-up
Keywords: Bio-diesel Fuels; Heavy-duty Injector; Mie-Scattering; Natural Flame Luminosity; OH* Chemiluminescence; Schlieren